MANAGEMENT OF THE USE OF PLAY-DOUGH MEDIA IN ENHANCING FINE MOTOR SKILLS OF CHILDREN AGED 4-5 YEARS - Nurhayati; Syamsuddin; Muhammad Rusmin B (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This classroom action research addressed the limited development of fine motor skills among children aged 4–5 years at TK Negeri Bonto Sinjai Tengah, where the initial learning process was characterized by low engagement and the lack of effective learning media. Grounded in constructivist theory and experiential learning, playdough was managed as a medium to create meaningful and enjoyable activities. The purpose of this study was to improve both the process of teaching and learning and the achievement of children’s fine motor skills through iterative action cycles. The research was designed as classroom action research (Kemmis & McTaggart model), carried out in two cycles involving one teacher and children in a kindergarten class. Data were collected through observation, interviews, and documentation, then analyzed descriptively and qualitatively to capture improvements in behavior and learning outcomes. Findings revealed that each cycle contributed to positive changes: children became more skillful in manipulating objects, more creative in shaping materials, and more engaged in classroom activities. It was concluded that using playdough as a learning medium transformed classroom dynamics, strengthened the teacher’s role as facilitator, and encouraged active participation. This study contributes theoretically by reinforcing experiential learning models, practically by offering replicable strategies for teachers, and institutionally by suggesting policies that support the integration of concrete media in early childhood education.